British general practitioners' attitudes towards and usage of homeopathy: a systematic review of surveys. Issue 2 (9th April 2013) - Perry, Rachel; Watson, Leala K; Terry, Rohini; Onakpoya, Igho; Ernst, Edzard
Abstract Background General practitioners (GPs) often refer patients to complementary and alternative medicine practitioners. One of the more popular yet controversial therapies for patients to request is homeopathy. Objectives To assess GP/primary care physician involvement with and attitudes towards homeopathy. Methods Seven electronic databases were searched to identify all relevant UK surveys of GPs/primary care physicians conducted between 1995 and 2013. Data extraction of all included trials was conducted by three independent reviewers. Results Thirteen surveys (from 15 articles) met the inclusion criteria. Less than 10% of GPs treated patients with homeopathy directly; referral rates ranged from 4–73%. Views on the effectiveness of homeopathy ranged from 29–48.7%, and opinions on whether it should be funded by the UK National Health Service ranged from 19–64%. Three surveys reported on GP professional training levels in homeopathy and two investigated GP knowledge of the evidence base of homeopathy. Conclusions Homeopathy is currently being utilised by the UK medical profession to a minor degree. Referral rates vary considerably nationally but, on average, are low.